Cuento infantil y logro de aprendizaje en el área de comunicación en estudiantes de la IEIPSM N° 60756 Claverito, Iquitos 2022 - Tello Hernández, Inés (2023)
The objective of the research was to determine the relationship between children's story and learning achievement in the area of communication in students of IEIPSM N° 60756 “Claverito” Iquitos 2022. This study with a non-experimental quantitative approach of a descriptive - correlational type had a descriptive cross-sectional design. The population was 135 students and the sample was delimited by 70 students from the 6th grade of primary school sections A, B, C and D, from IEIPSM No. 60756 “Claverito” Iquitos, enrolled in 2022. The technique that was used in the collection The data was the interview and documentary record and as instruments, the questionnaire and the report cards. For data processing, the statistical program Statistical package for social sciences (SPSS), version 26 in Spanish and Excel spreadsheet were used. For data analysis and interpretation, the chi square test was used (X2 c) < X2 0.05, Spearman's Rho correlation with a value of 0.28 and bilateral significance of p= 0.001 < 0.005. The hypothesis was accepted: there is a relationship between children's story and learning achievement in the area of communication in 6th grade students of IEIPSM N° 60756 “Claverito” Iquitos 2022.